Perceptions of Early Marriage Among Young People in Kyrgyzstan (Global Journal of Medical Research, 2022)
Despite legislation outlawing child marriage in Kyrgyzstan in 2017, the practice continues today. Early marriage is driven by social norms around religion, honor, financial stability, and restrictive gender roles. Participatory research activities were implemented with 12 adolescents in Kyrgyzstan Osh and the rural town of Chuy. Activities explored the perceptions of male and female youth around early marriage, gender norms, the consequences and benefits of marriage, and their autonomy in deciding who and when to wed. Responses from adolescents in the study were analyzed for themes by gender to reveal patterns in social norms around early marriage in Kyrgyzstan. Data showed that adolescents overwhelmingly did not support early marriage and expressed anxiety, shame, or concern about this topic. Interventions to prevent early marriage in Kyrgyzstan should advocate for girls' education and career opportunities and raise family and community awareness about the harms of child marriage.
Keywords: adolescence; culture/ethnic practices; gender; global/international issues; qualitative methods